Niobium uranium phosphate adsorbent and preparation method and application thereof

A niobium uranium phosphate adsorbent with high adsorption capacity and selectivity for uranyl ions is produced by reacting niobium oxalate with phosphoric acid, addressing the inefficiencies of existing adsorbents and offering rapid uranium removal with high selectivity and cost-effectiveness.

CN119218950APending Publication Date: 2024-12-31INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410157198.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-04
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing uranium adsorbents face challenges in achieving high adsorption capacity, selectivity, and fast adsorption rates for uranyl ions, particularly in the presence of competing ions, and are costly and complex to produce.

Method used

A niobium uranium phosphate adsorbent is prepared by reacting niobium oxalate with phosphoric acid in concentrated acid under controlled conditions, resulting in a specific crystal form with high affinity and selectivity for uranyl ions.

Benefits of technology

The adsorbent exhibits a uranium adsorption capacity of over 2400 mg/g, fast adsorption kinetics of ≤1 min, and high selectivity for uranyl ions, outperforming competing ions with a separation factor ≥40, while being cost-effective and simple to produce.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218950A_ABST
    Figure CN119218950A_ABST
Patent Text Reader

Abstract

The invention provides a niobium-uranium phosphate oxide adsorbent and a preparation method and application thereof, and the preparation method comprises the following steps: adding phosphoric acid into a suspension containing niobium oxalate and concentrated acid, and heating for reaction to obtain the niobium-uranium phosphate oxide adsorbent. The uranium oxyniobium phosphate adsorbent prepared by the method has high adsorption capacity and rapid adsorption kinetics to uranyl ions, and shows high selectivity to uranyl ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption, and relates to a niobium uranium oxyphosphate adsorbent and a preparation method and application thereof. Background Art

[0002] In the international energy environment where the demand for nuclear energy is growing, the number of nuclear power plants is increasing rapidly every year. Uranium mining will bring about a greater environmental resource crisis. On the one hand, the increase in uranium consumption has accelerated the depletion of uranium ore; on the other hand, the uranium-containing wastewater produced during uranium mining has caused great harm to human health, such as irreversible radiation damage, acute kidney and liver damage, and even death in severe cases. Therefore, the separation, enrichment and recovery of uranium in uranium-containing wastewater has become an urgent global environmental issue.

[0003] Many technologies have been used to remove uranium from wastewater, such as solvent extraction, electrochemical deposition, chemical precipitation, photoreduction and adsorption. Considering the operating cost, removal efficiency and process difficulty, the development of efficient and low-cost uranium removal adsorbents is the key to solving this environmental problem.

[0004] Researchers have developed various types of uranyl ion adsorption materials. CN113026147B discloses a method for preparing nanofiber-shaped calcium hydrogen phosphate. Calcium hydrogen phosphate is prepared by a simple nano-microemulsion method. Different nano-morphologies can be obtained by this method. The fibrous calcium hydrogen phosphate shows good uranium adsorption performance in seawater uranium extraction. The patent also provides a method for preparing phosphate inorganic adsorbents: using surfactant Pluronic-F127 and mesitylene to prepare a stable and uniform water-in-oil type microemulsion; weighing calcium source and phosphate source and ultrasonically dissolving to obtain an inorganic salt solution; slowly adding the inorganic salt solution to the above microemulsion to allow the inorganic ions and microemulsion to self-assemble; adding ammonia water to a beaker, adding ethanol water with a volume ratio of 1:1, centrifuging after ultrasonic dispersion, extracting, washing, and freeze-drying to obtain the final product. However, it is difficult for the above materials to have high adsorption capacity, high selectivity and fast adsorption rate.

[0005] Therefore, there is an urgent need for a uranium adsorbent that has high adsorption capacity, high selectivity and fast adsorption rate. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a niobium uranium phosphate adsorbent and a preparation method and application thereof. The method of the present invention can be used to prepare a niobium uranium phosphate adsorbent of a specific crystal form, which has a high adsorption capacity and fast adsorption kinetics for uranyl ions, exhibits high affinity for uranyl ions, and exhibits high selectivity for uranyl ions in the presence of multiple competing ions.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a niobium uranium oxyphosphate adsorbent, the preparation method comprising:

[0009] Phosphoric acid is added into a suspension containing niobium oxalate and concentrated acid, and the mixture is heated for reaction to obtain the niobium uranium oxyphosphate adsorbent.

[0010] The present invention provides a method for preparing a niobium uranium phosphate adsorbent. Under heating conditions, niobium oxalate reacts with phosphoric acid in concentrated acid to obtain a niobium uranium phosphate adsorbent of a specific crystal form. The niobium uranium phosphate adsorbent has a high adsorption capacity and fast adsorption kinetics for uranyl ions, exhibits high affinity for uranyl ions, and exhibits high selectivity for uranyl ions in the presence of multiple competing ions. In addition, the synthetic raw materials are inexpensive and the preparation process is simple. The excellent adsorption and separation performance and commercialization advantages of the adsorbent indicate that it has excellent prospects in the field of adsorption and separation.

[0011] Preferably, the concentrated acid includes at least one of concentrated sulfuric acid, concentrated hydrochloric acid and concentrated nitric acid, preferably concentrated nitric acid.

[0012] In the present invention, phosphoric acid and niobium oxalate undergo a replacement reaction in a high proton concentration environment and a low water content environment provided by concentrated nitric acid to obtain a niobium uranium oxyphosphate adsorbent that is poorly soluble in water.

[0013] Preferably, the mass fraction of the concentrated nitric acid is 68-90%, for example, it can be 68%, 69%, 70%, 71%, 72%, 75%, 80% or 90%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the mass fraction of the concentrated hydrochloric acid is 36-38%, for example, it can be 36%, 36.2%, 36.4%, 36.6%, 36.8%, 37%, 37.5% or 38%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the mass fraction of the concentrated sulfuric acid is 95-98%, for example, 95%, 96%, 97% or 98%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0016] Preferably, in the suspension containing niobium oxalate and concentrated acid, the mass volume ratio of niobium oxalate to concentrated acid is (0.2-10) g:(0.5-150) mL, wherein the selection range of niobium oxalate (0.2-10) g can be, for example, 0.2 g, 0.3 g, 0.4 g, 0.5 g, 1 g, 1.25 g, 1.5 g, 2 g, 2.4 g, 2.5 g, 3 g, 4 g, 5 g, 6 g, 7 g, 8 g, 9 g or 10 g, and the selection range of concentrated acid (0.5-150) mL can be, for example, 0.5 mL, 1 mL, 5 mL, 9 mL, 10 mL, 20 mL, 50 mL, 80 mL, 100 mL, 120 mL or 150 mL, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0017] In the present invention, if the mass volume ratio of niobium oxalate to concentrated acid is too high, the product will contain a large amount of oxalate impurities; if the mass volume ratio of niobium oxalate to concentrated acid is too low, a colloidal product will be formed.

[0018] Preferably, the volume ratio of the phosphoric acid to the concentrated acid is 1:(1-30), for example, it can be 1:1, 1:2, 1:5, 1:8, 1:10, 1:15, 1:18, 1:20, 1:25 or 1:30, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present invention, if the volume ratio of the phosphoric acid to the concentrated acid is too high, hydrogen phosphate will be formed to affect the properties of the product; if the volume ratio of the phosphoric acid to the concentrated acid is too low, the adsorption performance of the product will be affected, and raw materials will be wasted, resulting in a low yield.

[0020] Preferably, the temperature of the heating reaction is 100-150°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 100-125°C.

[0021] Preferably, the heating reaction time is 0.5-30h, for example, it can be 0.5h, 1h, 1.5h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 18h, 20h, 25h or 30h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1-18h.

[0022] Optionally, the heating reaction is carried out under oil bath conditions.

[0023] Preferably, the reaction is accompanied by stirring, and the stirring speed is 200-550 r / min, for example, it can be 200 r / min, 300 r / min, 400 r / min, 500 r / min or 550 r / min, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 400-550 r / min.

[0024] As a preferred technical solution of the present invention, the preparation method specifically comprises:

[0025] (1) mixing niobium oxalate and concentrated acid, and subjecting them to ultrasonic dispersion for 1-60 min (e.g., 1 min, 2 min, 5 min, 10 min, 20 min, 30 min, 50 min or 60 min, etc.) to obtain a suspension containing niobium oxalate and concentrated acid;

[0026] Wherein, in the suspension containing niobium oxalate and concentrated acid, the mass volume ratio of niobium oxalate and concentrated acid is (0.2-10) g: (0.5-150) mL;

[0027] (2) adding phosphoric acid to the suspension containing niobium oxalate and concentrated acid, heating to 100-150° C. for reaction for 0.5-30 h at a stirring speed of 200-550 r / min, and then centrifuging, washing and drying at 50-120° C. (for example, 50° C., 60° C., 80° C., 100° C. or 120° C.) to obtain the niobium uranium phosphate adsorbent;

[0028] Wherein, the volume ratio of the phosphoric acid to the concentrated acid is 1:(1-30).

[0029] In a second aspect, the present invention provides a niobium uranium oxyphosphate adsorbent, wherein the niobium uranium oxyphosphate adsorbent is prepared by the preparation method described in the first aspect.

[0030] In a third aspect, the present invention provides an application of the niobium uranium oxyphosphate adsorbent described in the second aspect, wherein the niobium uranium oxyphosphate adsorbent is applied to treat uranium-containing wastewater.

[0031] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention provides a method for preparing a niobium uranium phosphate adsorbent. Under heating conditions, niobium oxalate reacts with phosphoric acid in concentrated acid to obtain a niobium uranium phosphate adsorbent of a specific crystal form. The niobium uranium phosphate adsorbent has a high adsorption capacity and fast adsorption kinetics for uranyl ions, exhibits high affinity for uranyl ions, and exhibits high selectivity for uranyl ions in the presence of multiple competing ions. In addition, the synthetic raw materials are inexpensive and the preparation process is simple. The excellent adsorption and separation performance and commercialization advantages of the adsorbent indicate that it has excellent prospects in the field of adsorption and separation.

[0034] The uranium adsorption capacity of the niobium uranium phosphate adsorbent provided by the present invention can reach more than 2400 mg / g, the adsorption kinetic equilibrium time is ≤1 min, and the adsorption capacity of most competing metal ions (such as Na + , K + , Ca 2+ Mg 2+ , Cu 2+ or Zn 2+ The separation factor of the samples is ≥40. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a scanning electron microscope image of the niobium uranium oxyphosphate adsorbent provided in Example 1 of the present invention.

[0036] Figure 2 This is an X-ray diffraction diagram of the niobium uranium oxyphosphate adsorbent provided in Example 1 of the present invention before and after adsorption.

[0037] Figure 3 This is an X-ray photoelectron spectrum of the niobium uranium oxyphosphate adsorbent provided in Example 1 of the present invention before and after adsorption.

[0038] Figure 4 This is a P2p spectrum in the X-ray photoelectron spectrum of the niobium uranium oxyphosphate adsorbent provided in Example 1 of the present invention before and after adsorption.

[0039] Figure 5 This is the O1s spectrum of the niobium uranium oxyphosphate adsorbent provided in Example 1 of the present invention before and after adsorption in the X-ray photoelectron spectrum.

[0040] Figure 6 Changes in adsorption capacity of the niobium uranium oxyphosphate adsorbent provided in Example 1, Example 4 and Comparative Example 1 of the present invention at different pH values. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0042] Example 1

[0043] This embodiment provides a method for preparing a niobium uranium oxyphosphate adsorbent, the preparation method comprising:

[0044] (1) 1.25 g of niobium oxalate was dissolved in 9 mL of 68% concentrated nitric acid by ultrasonication for 30 min, and 1 mL of phosphoric acid was added to obtain a mixed solution;

[0045] (2) The mixed solution obtained in step (1) is reacted for 8 hours under the conditions of heating at a constant temperature of 110° C. and stirring at a rotation speed of 400 r / min. After the reaction is completed, the product is transferred to a centrifuge tube for centrifugation. The precipitate obtained by centrifugation is washed three times with deionized water, rinsed once with anhydrous ethanol, vacuum dried at 65° C. overnight, and ground into fine powder to obtain the niobium uranium phosphate adsorbent.

[0046] The morphology of the niobium uranium phosphate adsorbent provided in Example 1 was characterized by scanning electron microscopy (British Zeiss, Sigma 300). Figure 1 As shown, the apparent morphology of niobium oxyphosphate is microspheres formed by stacking nanosheets with a diameter of 5 μm.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that the reaction time in step (2) is 4 hours, and the remaining steps and parameters are the same as those in embodiment 1.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the reaction time in step (2) is 12 h, and the remaining steps and parameters are the same as those in embodiment 1.

[0051] Example 4

[0052] The difference between this embodiment and embodiment 1 is that the reaction time in step (2) is 18 h, and the remaining steps and parameters are the same as those in embodiment 1.

[0053] Example 5

[0054] The difference between this embodiment and embodiment 1 is that the reaction time in step (2) is 2 h, and the remaining steps and parameters are the same as those in embodiment 1.

[0055] Example 6

[0056] The difference between this embodiment and embodiment 1 is that the volume of phosphoric acid added is 5 mL, and the remaining steps and parameters are the same as those in embodiment 1.

[0057] Example 7

[0058] The difference between this embodiment and embodiment 1 is that the volume of phosphoric acid added is 3 mL, and the remaining steps and parameters are the same as those in embodiment 1.

[0059] Example 8

[0060] The difference between this embodiment and embodiment 1 is that the mass of niobium oxalate added is 2.5 g, and the other steps and parameters are the same as those in embodiment 1.

[0061] Example 9

[0062] The difference between this embodiment and embodiment 1 is that the mass of niobium oxalate added is 0.3 g, and the other steps and parameters are the same as those in embodiment 1.

[0063] Example 10

[0064] The difference between this embodiment and embodiment 1 is that the volume of phosphoric acid added is 0.5 mL, and the remaining steps and parameters are the same as those in embodiment 1.

[0065] Embodiment 11

[0066] The difference between this embodiment and embodiment 1 is that an equal volume of concentrated nitric acid with a mass fraction of 68% is replaced by concentrated sulfuric acid with a mass fraction of 95%, and the remaining steps and parameters are the same as those in embodiment 1.

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that an equal volume of concentrated nitric acid is replaced by deionized water, and the remaining steps and parameters are the same as those in Example 1.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that the mass of niobium oxalate is replaced by niobium pentoxide, and the remaining steps and parameters are the same as those in Example 1.

[0071] Performance Testing

[0072] (1) Preparation of uranium solution

[0073] Accurately weigh 0.4220g UO 2 (NO 3 ) 2 6H 2 O in a 50mL beaker, add deionized water and transfer to a 500mL volumetric flask to make up the volume, shake well, and obtain a uranium stock solution with a concentration of 400mg / L. Use this uranium stock solution to dilute and obtain uranium solutions of different concentrations.

[0074] (2) Investigate the effect of pH value of uranium solution on uranium adsorption capacity

[0075] Weigh 5 mg of the niobium uranium phosphate adsorbent provided in Example 1 into a 125 mL plastic vial and add 0.1 mol / L HNO 3The pH values ​​of the uranium solution were adjusted to 3, 4, 5, 6, 7, 8 and 9 with 0.1 mol / L NaOH, and 100 mL of the uranium solution with a pH adjusted to 20 mg / L was added. The solution was placed in a constant temperature shaking incubator (25°C, 180 rpm) and oscillated at constant temperature for 10 min to achieve adsorption equilibrium. The supernatant was taken with a syringe and filtered with a 0.22 μm water filter. The uranium concentration of the solution before and after adsorption was determined using an inductively coupled plasma optical emission spectrometer (ICP-OES), and the adsorption capacity q was calculated according to the following formula (1): e :

[0076]

[0077] Among them, C 0 (mg / L) is the uranium concentration in the initial solution; C e (mg / L) is the uranium concentration in the solution at adsorption equilibrium; V(L) is the volume of the solution; m(g) is the mass of the adsorbent added. According to the adsorption capacity results, Figure 6 As shown, the optimal pH was determined to be 6.0 and was used in subsequent adsorption experiments.

[0078] (3) Investigate the effect of different adsorption times on uranium adsorption capacity

[0079] Weigh 20 mg of the uranium niobium phosphate adsorbent provided in Example 1 into a 500 mL plastic bottle, add 500 mL of a uranium solution with a concentration of 20 mg / L and a pH value of 6, place in a constant temperature shaking shaker (25°C, 180 rpm) for constant temperature shaking, take samples at different adsorption time points of 1 min, 3 min, 5 min, 8 min, 10 min, 12 min, 14 min, 16 min and 20 min, take the supernatant with a syringe, filter with a 0.22 μm water filter, and use ICP-OES to determine the uranium concentration of the solution before and after adsorption. Its kinetic data conforms to the pseudo-first-order kinetic model, and adsorption equilibrium can be reached in about 1 min.

[0080] (4) Testing the uranium adsorption capacity corresponding to Examples 1-11 and Comparative Examples 1-2 and exploring the optimal initial concentration of the uranium solution

[0081] For the products prepared in Examples 1-11 and Comparative Examples 1-2, 5 mg of each product was weighed into 6 125 mL plastic vials, and 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L and 80 mg / L of uranium solution with a pH value of 6 and a volume of 100 mL were added to each plastic vial, respectively, and placed in a constant temperature shaking shaker (25°C, 220 rpm) for constant temperature shaking for 20 min to reach adsorption equilibrium, the supernatant was taken with a syringe, filtered with a 0.22 μm water filter, and the uranium concentration of the solution before and after adsorption was determined using ICP-OES, and the adsorption capacity of each embodiment and comparative example was calculated and fitted. The test results are shown in Table 1.

[0082] The isotherm data corresponding to Example 1 conform to the Langmuir adsorption isotherm model, and the simulated maximum adsorption capacity is 2436.82 mg / g, from which it is judged that the optimal initial concentration of the uranium solution is 20 mg / L.

[0083] (5) Adsorption equilibrium time of test examples 1-11 and comparative examples 1-2

[0084] Weigh 20 mg of the uranium niobium phosphate adsorbent provided in the above examples and comparative examples into a 500 mL plastic bottle, add 500 mL of a uranium solution with a concentration of 20 mg / L and a pH value of 6, place in a constant temperature shaking shaker (25°C, 180 rpm) for constant temperature shaking, take a sample every 1 min, take the supernatant with a syringe, filter with a 0.22 μm water filter, and use ICP-OES to determine the uranium concentration of the solution before and after adsorption. Its kinetic data conforms to the pseudo-first-order kinetic model, and the kinetic equilibrium time, i.e., the adsorption equilibrium time, is obtained after fitting.

[0085] The test results are shown in Table 1.

[0086] (6) Exploring the selectivity of niobium uranium phosphate adsorbent

[0087] Weigh 5 mg of the niobium uranium phosphate adsorbent provided in Example 1 into a 125 mL plastic vial and add it to 100 mL of uranium solution containing interfering ions, wherein the competing interfering ion is Na + , K + , Ca 2+ Mg 2+ , Cu 2+ and Zn 2+ The concentrations of uranium ions and interfering ions were both 10 mg / L. The samples were placed in a constant temperature shaking incubator (25°C, 220 rpm) and oscillated for 20 min to achieve adsorption equilibrium. The supernatant was taken with a syringe and filtered with a 0.22 μm water filter. The uranium concentration and interfering ion concentration of the solution before and after adsorption were determined using ICP-OES.

[0088] According to the uranium concentration of the solution before and after adsorption and the above formula (1), the uranium adsorption capacity of the adsorbent is calculated, and according to the concentration of a certain interfering ion before and after adsorption and the above formula (1), the adsorption capacity of the adsorbent for a certain interfering ion is calculated, and then according to formula (2), the distribution coefficient of uranium and the distribution coefficient of the above interfering ion are respectively calculated;

[0089]

[0090] Among them, K d is the distribution coefficient, q e (mg / g) is the adsorption capacity at equilibrium, C e (mg / L) is the ion concentration in the solution at adsorption equilibrium.

[0091] By calculating the ratio of the distribution coefficient of uranium to the distribution coefficient of a certain interfering ion, the separation factor is obtained. + , K + , Ca 2+ Mg 2+ , Cu 2+ or Zn 2+ The separation factors of metal competing ions were all ≥40. This indicates that the niobium uranium phosphate adsorbent has a high selectivity for uranyl ions.

[0092] (7) Characterization test

[0093] a) The niobium uranium phosphate adsorbent provided in Example 1 was tested before and after adsorption using an X-ray diffractometer (PANalytical BV, Empyrean, The Netherlands), wherein the adsorption method was the method of the above-mentioned test (5).

[0094] Test results such as Figure 2 As shown, NbP-8 represents before adsorption, and U-NbP-8 represents after adsorption. In the X-ray diffraction (XRD) spectrum of Example 1, by comparing the standard PDF card, it can be known that the main crystalline phase synthesized is PDF#76-2124, and after adsorption, the peak around 25.225° on the XRD spectrum disappears, indicating that the corresponding (101) crystal plane disappears, proving that uranyl ions are inserted into the lattice gap in the form of heteroatoms, reflecting the reason for the high adsorption capacity of the material for uranium.

[0095] b) The niobium uranium oxyphosphate adsorbent provided in Example 1 was tested before and after adsorption using an X-ray photoelectron spectrometer (Thermo, USA), wherein the adsorption test method used was the method of test (5) above.

[0096] The measured X-ray photoelectron spectroscopy (XPS) is shown in the figure Figure 3As shown, NbP-8 represents before adsorption, and U-NbP-8 represents after adsorption; in the full XPS spectrum, after the adsorption of Example 1, new binding energy peaks appear at 392.95 eV and 382.05 eV, which are characteristic peaks of uranyl ions, namely U4f5 / 2 and U4f7 / 2, respectively;

[0097] In the XPS P2p spectrum, Figure 4 As shown, NbP-8 represents before adsorption, and U-NbP-8 represents after adsorption; the binding energy peaks at 134.45eV and 133.55eV of niobium oxyphosphate are respectively attributed to P2p 1 / 2 and P2p 3 / 2 ,After adsorption, these two peaks move toward the direction of high binding energy;

[0098] In the XPS O1s spectrum, Figure 5 As shown in the figure, NbP-8 represents before adsorption, and U-NbP-8 represents after adsorption; the binding energy peaks at 534.50eV, 534.20eV and 532.35eV of niobium oxyphosphate are attributed to OH, PO and Nb-O respectively. After adsorption, these three peaks move toward the direction of low binding energy. The peak position changes in the spectra of P and O indicate that the coordination is carried out by oxygen. After coordination with uranium, the electron cloud density between atoms adjacent to O is reduced, and the binding energy is reduced.

[0099] Table 1

[0100]

[0101]

[0102] In Table 1, it can be seen from Example 1 that the niobium uranium phosphate adsorbent prepared by the preparation method of the present invention exhibits a uranium adsorption capacity of up to 2436.82 mg / g and an adsorption equilibrium time of ≤1 min, i.e., extremely fast adsorption kinetics. The niobium uranium phosphate adsorbent prepared in Example 2 also exhibits a relatively high uranium adsorption capacity and extremely fast adsorption kinetics.

[0103] It can be seen from Examples 1-5 that when the reaction time in step (2) is too short or too long, the uranium adsorption capacity of the niobium uranium phosphate adsorbent will decrease.

[0104] It can be seen from Example 1, Example 6-7 and Example 10 that when the amount of phosphoric acid added is too much, the volume ratio of phosphoric acid and concentrated nitric acid is too large, hydrogen phosphate is formed, the properties of the product are affected, and the uranium adsorption capacity is reduced; when the amount of phosphoric acid added is too little, the volume ratio of phosphoric acid and concentrated nitric acid is too small, which will result in less product generated, loss of raw materials, and will also affect the adsorption performance of the product.

[0105] It can be seen from Example 1 and Examples 8-9 that when the amount of niobium oxalate added is too large, the mass volume ratio of niobium oxalate and concentrated nitric acid is too large, which will cause the product to contain a large amount of oxalate impurities, resulting in a decrease in uranium adsorption capacity, slower adsorption kinetics, and a longer adsorption equilibrium time; when the amount of niobium oxalate added is too small, the mass volume ratio of niobium oxalate and concentrated nitric acid is too small, a colloidal product will be formed, and the adsorption performance will be reduced.

[0106] It can be seen from Example 1 and Example 11 that when concentrated sulfuric acid is used to prepare the niobium uranium phosphate adsorbent, its adsorption effect is worse than that of the niobium uranium phosphate adsorbent prepared by concentrated nitric acid.

[0107] It can be seen from Example 1 and Comparative Example 1 that when the reaction is not carried out under the condition of using concentrated nitric acid as a solvent but using deionized water, the adsorption kinetics of the prepared niobium uranium oxyphosphate adsorbent is slower and the uranium adsorption capacity is lower.

[0108] It can be seen from Example 1 and Comparative Example 2 that when niobium pentoxide is used as the raw material, the prepared material cannot adsorb uranium.

[0109] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a niobium uranium oxyphosphate adsorbent, characterized in that: The preparation method comprises: Phosphoric acid is added into a suspension containing niobium oxalate and concentrated acid, and the mixture is heated for reaction to obtain the niobium uranium oxyphosphate adsorbent.

2. The preparation method according to claim 1, characterized in that: The concentrated acid includes at least one of concentrated sulfuric acid, concentrated hydrochloric acid and concentrated nitric acid, preferably concentrated nitric acid.

3. The preparation method according to claim 2, characterized in that: The mass fraction of the concentrated nitric acid is 68-90%; Preferably, the mass fraction of the concentrated hydrochloric acid is 36-38%; Preferably, the mass fraction of the concentrated sulfuric acid is 95-98%.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the suspension containing niobium oxalate and concentrated acid, the mass volume ratio of niobium oxalate to concentrated acid is (0.2-10) g: (0.5-150) mL.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The volume ratio of the phosphoric acid to the concentrated acid is 1:(1-30).

6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the heating reaction is 100-150°C, preferably 100-125°C; Preferably, the heating reaction time is 0.5-30h, preferably 1-18h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The reaction is accompanied by stirring at a speed of 200-550 r / min, preferably 400-550 r / min.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method specifically comprises: (1) mixing niobium oxalate and concentrated acid, and performing ultrasonic dispersion for 1-60 minutes to obtain a suspension containing niobium oxalate and concentrated acid; Wherein, in the suspension containing niobium oxalate and concentrated acid, the mass volume ratio of niobium oxalate and concentrated acid is (0.2-10) g: (0.5-150) mL; (2) adding phosphoric acid to the suspension containing niobium oxalate and concentrated acid, heating to 100-150° C. for reaction for 0.5-30 h at a stirring speed of 200-550 r / min, and then centrifuging, washing and drying at 50-120° C. to obtain the niobium uranium phosphate adsorbent; Wherein, the volume ratio of the phosphoric acid to the concentrated acid is 1:(1-30).

9. A niobium uranium oxyphosphate adsorbent, characterized in that: The niobium uranium oxyphosphate adsorbent is prepared by the preparation method according to any one of claims 1-8.

10. Use of the niobium uranium oxyphosphate adsorbent according to claim 9, characterized in that: The niobium uranium oxyphosphate adsorbent is used for treating uranium-containing wastewater.

Citation Information

Patent Citations

  • A method for preparing calcium hydrogen phosphate nanofibers for efficient uranium separation

    CN113026147B